PENGEMBANGAN SISTEM EDUKASI PENCEGAHAN PENYAKIT DIARE BERBASIS DEVELOPMENT OF CIVIL SOCIETY DI KOTA PAREPARE - Usman Usman; Lilis Suriani (Dian Nuswantoro Semarang, 2016)
Based on the report of Pare-Pare City Health Office, the incidence of diarrhea continued to increase during the last two years, in 2011 there were 6543 cases (2.23%) and 2731 casesÂ (2.36% ) in 2012. The study aims to find out the changes of knowledge level and attitudes before and after the education regarding the prevention of diarrheal disease. This study design was quasi-experimental with one group pretest-posttest. Sampling technique was accidental sampling. The number of samples were 273 peoples.Â The intervention used several methods, such asÂ flyer, fipchart and banners. The instrument was questionnaire and data analyzed by T-test. The survey results revealed there was increasing in the level of knowledge about the prevention of diarrheal disease after being given education (post test I) from 3.31 points to 9.01 points (p-value 0.001) while the attitude jumped from 5.11 points to 8.92 points (p-value 0.004). In the post test II, the average of knowledge score increased from 3.31 points to 9.27 points (p-value 0.000) and the attitude climbed from 5.11 points to 9.48 (p-value 0.000) Keywords: Diarrhea, Development of Civil Society